Academic collaborative models fostering the translation of physiological in vitro systems from basic research into drug discovery. Issue 6 (June 2021) - Silvestri, Alessandra; Vicente, Francisca; Vicent, María J.; Stechmann, Bahne; Fecke, Wolfgang
Abstract : The success of preclinical drug discovery strongly relies on the ability of experimental models to resemble human pathophysiology. The number of compounds receiving approval for clinical use is limited, and this has led to the development of more physiologically relevant cellular models aimed at making preclinical results more prone to be successfully translated into clinical use. In this review, we summarize the technologies available in the field of high-throughput screening (HTS) using complex cellular models, and describe collaborative initiatives, such as EU-OPENSCREEN, which can efficiently support researchers to easily access state-of-the-art chemical biology platforms for improving the drug discovery process. Teaser: European collaborative networks represent a promising approach for fostering the translation of physiological in vitro models (co-cultures, 3D cell cultures, and patient-derived organoids) from basic research into early-stage drug discovery.